Answer:
[tex]g^{-1}(0) = 8[/tex]
Explanation:
Given
[tex]g=\{(-9,-4),(-7,3),(0,-6),(8,0)\}[/tex]
[tex]h(x) = 4x + 9[/tex]
Required
Find [tex]g^{-1}(0)[/tex]
A relation is represented as: [tex](x,y)[/tex]
And the following relationships exist between x and y
[tex]y = g(x)[/tex]
and
[tex]x =g^{-1}(y)[/tex]
So: [tex]g^{-1}(0)[/tex] implies that:
[tex]x = g^{-1}(0)[/tex]
Which means that: we look for the corresponding value of x where y = 0.
Hence:
[tex]x = g^{-1}(0) = 8[/tex]
[tex]g^{-1}(0) = 8[/tex]